PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT.ARARA ABADI SINARMAS FORESTRY - Dewi, Dewi; Hardi, Hardi; Waldelmi, Idel (Komunitas Manajemen Kompetitif, 2022)
Business companies engaged in manufacture must be able to compete fiercely in marketing their products. The employee performance factors are important points that had to be considered by the company. Employee performance is measured by work quality, quantity, accuracy, effectiveness, independence, and commitment to work. Employee performance is closely related to work motivation and discipline, so to produce good performance requires motivation and work discipline. The type of data used in this research is quantitative data. Data mining is carried out by distributing questionnaires, field observations, and collecting documents or archives. The population in this study were 1460 employees of PT. Arara Abadi Sinarmas Forestry. The research sample was 314 respondents who were calculated using Slovin's formula. The sampling technique used is random sampling. From the results of this study, it can be concluded that, 1) work of motivation affects the performance of the employees of PT. Arara Abadi Sinarmas Forestry; 2) work discipline affects the performance of the employees of PT. Arara Abadi Sinarmas Forestry; 3) motivation and work discipline simultaneously influence the performance of employees of PT. Arara Abadi Sinarmas Forestry. Keywords: Work Motivation, Work Discipline, and Employee Performance